Correlation Coefficients of Complex Fuzzy Sets and Their Application - Yasin Ali, Md; Hadi, Abedul (GANIT: Journal of Bangladesh Mathematical Society, 2024)
Complex fuzzy set (CFS) is an extension of the fuzzy set (FS) which can deal with ambiguity by allowing a complex-valued membership degree of an element of a universal set. A host of researchers studied the complex fuzzy sets in theoretical and practical due to their amplitude term and phase term membership degrees. At present, various applications of fuzzy correlation and correlation coefficients have emerged by numerous researchers. But most of the works are related to real fuzzy data. In this article, we introduce the concept of the correlation coefficient of the complex fuzzy sets and some of its related properties are described. Furthermore, an application of the correlation coefficient of the complex fuzzy sets in pattern recognition is illustrated. To show the reliability and validity of our technique, we explain a comparative study with the existing method. J. Bangladesh Math. Soc. 44.2 (2024) 028–038